2006
DOI: 10.2987/8756-971x(2006)22[433:eoelbe]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Eight Larvicidal Botanical Extracts from Khaya senegalensis and Daucus carota against Culex annulirostris

Abstract: The failure to discover a significant new class of insecticides has led many researchers back to biodiscovery studies in the search for new and economically viable alternatives. After a preliminary screening of botanical extracts using descending series of concentrations (1,000, 500, 100, 50, and 5 mg/liter), 8 extracts from 2 potential botanical agents, Khaya senegalensis (Desrousseaux) and Daucus carota L., were tested against 4th instars of Culex annulirostris (Skuse) following the standard World Health Org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The larvicidal activity of petroleum ether, ethanolic, aqueous extracts of dried leaves and fixed oil from the seeds of Caesalpinia bonduc (Family: Caesalpiniaceae) showed 100% mortality in 1% concentration of petroleum ether and ethanolic extract of leaf, whereas it was 55% in 2.5% concentration of aqueous extract and 92.6% in 2.5% concentration of fixed oil against the fourth instar larvae of C. quinquefasciatus (Saravanan et al 2007); the 100% larval mortality was found at 1,000 ppm in whole plant petroleum ether extract of C. colocynthis against the early fourth instar larvae of C. quinquefasciatus ); the compounds 4-gingerol (1), (6)-dehydrogingerdione (2) and (6) Control-nil mortality. Significant at p<0.05 level LC 50 lethal concentration that kills 50% of the exposed larvae, LC 90 lethal concentration that kills 90% of the exposed larvae, UCL upper confidence limit, LCL lower confidence limit, χ 2 chi-square, df degree of freedom (Shaalan et al 2006). Ethyl acetate soluble fractions of C. inophyllum and petroleum ether fraction of R. nasutus extracts showed very high larvicidal activity ranging from 3.91 to 9.39, 9.04 to 35.49 and 13.21 to 28.92 ppm of the active fractions of seed and leaf extracts of C. inophyllum and the leaf extract of R. nasutus, respectively, killing 50% of the treated larvae (Pushpalatha and Muthukrishnan 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The larvicidal activity of petroleum ether, ethanolic, aqueous extracts of dried leaves and fixed oil from the seeds of Caesalpinia bonduc (Family: Caesalpiniaceae) showed 100% mortality in 1% concentration of petroleum ether and ethanolic extract of leaf, whereas it was 55% in 2.5% concentration of aqueous extract and 92.6% in 2.5% concentration of fixed oil against the fourth instar larvae of C. quinquefasciatus (Saravanan et al 2007); the 100% larval mortality was found at 1,000 ppm in whole plant petroleum ether extract of C. colocynthis against the early fourth instar larvae of C. quinquefasciatus ); the compounds 4-gingerol (1), (6)-dehydrogingerdione (2) and (6) Control-nil mortality. Significant at p<0.05 level LC 50 lethal concentration that kills 50% of the exposed larvae, LC 90 lethal concentration that kills 90% of the exposed larvae, UCL upper confidence limit, LCL lower confidence limit, χ 2 chi-square, df degree of freedom (Shaalan et al 2006). Ethyl acetate soluble fractions of C. inophyllum and petroleum ether fraction of R. nasutus extracts showed very high larvicidal activity ranging from 3.91 to 9.39, 9.04 to 35.49 and 13.21 to 28.92 ppm of the active fractions of seed and leaf extracts of C. inophyllum and the leaf extract of R. nasutus, respectively, killing 50% of the treated larvae (Pushpalatha and Muthukrishnan 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Thomas et al (2004) reported that the essential oil of I. cairica possessed remarkable larvicidal properties as it could produce 100% mortality in the larvae of Culex tritaeniorhynchus, A. aegypti, A. stephensi, and C. quinquefasciatus mosquitoes at concentrations ranging from 100 to 170 ppm. The median lethal concentration (LC 50 ) values for Khaya senegalensis using acetone, ethanol, hexane, and methanol extracts were 20.12, 5.1, 5.08, and 7.62 mg/l, respectively and the LC 50 values for Daucus carota were 236.00, 36.59, 77.19, and 241.8 mg/l, respectively against Culex annulirostris (Shaalan et al 2006). Komalamisra et al (2005) have reported that the petroleum ether extract of Rhinacanthus nasutus possessed larvicidal effects with LC 50 values between 3.9 and 11.5 mg/l and Derris elliptica showed LC 50 values between 11.2 and 18.84 mg/l against A. Control-nil mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Shaalan et al (2006) have reported that the LC 50 value of acetone extracts of Khaya saenegalensis and Daucus carota were 20.12 and 236.00 mg/l, respectively, against 4th-instars of Culex annulirostris. Larvicidal activity of acetone extracts of Murraya koenigii, Coriandrum sativum, Ferula asafoetida, and Trigonella foenum graceum reported maximum activity ranging 25-900 ppm against A. aegypti (Harve and Kamath 2004).…”
Section: Resultsmentioning
confidence: 99%